A Flat-spectrum Radio Transient at 122 Mpc Consistent with an Emerging Pulsar Wind Nebula - Dillon Z. Dong; Gregg Hallinan (The Astrophysical Journal, 2023)
We report the discovery and follow-up observations of VT 1137–0337, an unusual radio transient found in our systematic search for extragalactic explosions in the Very Large Array Sky Survey. It is located in the brightest region of a dwarf starburst galaxy at a luminosity distance of 121.6 Mpc. Its 3 GHz luminosity is comparable to luminous radio supernovae associated with dense circumstellar interaction and relativistic outflows. However, its broadband radio spectrum—proportional to ν ^−0.35 over a range of ≳10× in frequency and fading at a rate of 5% yr ^–1 —cannot be directly explained by the shock of a stellar explosion. Jets launched by various classes of accreting black holes also struggle to account for VT 1137–0337's combination of observational properties. Instead, we propose that VT 1137–0337 is a decades-old pulsar wind nebula that has recently emerged from within the free–free opacity of its surrounding supernova ejecta. If the nebula is powered by spin-down, the central neutron star should have a surface dipole field of ∼10 ^13 –10 ^14 G and a present-day spin period of ∼10–100 ms. Alternatively, the nebula may be powered by the release of magnetic energy from a magnetar. Magnetar nebulae have been proposed to explain the persistent radio sources associated with the repeating fast radio bursts FRB 121102 and FRB 190520B. These FRB persistent sources have not previously been observed as transients but do bear a striking resemblance to VT 1137–0337 in their radio luminosity, spectral index, and host galaxy properties.